2005
DOI: 10.1038/sj.eye.6701916
|View full text |Cite
|
Sign up to set email alerts
|

Screening for age-related macular degeneration using nonstereo digital fundus photographs

Abstract: Age-related macular degeneration (AMD) is a disease with significant visual morbidity and accounts for the majority of blind registrations in the developed world including the UK. Certain forms of neovascular AMD are amenable to treatment but require expeditious referral to a retinal specialist. Aim To evaluate the possibility of using nonstereo fundus photographs as a low-cost screening tool for neovascular AMD. Design Retrospective review of patients referred to the macular clinic of a teaching hospital in L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…The best result achieved was sensitivity of 82%. It is worth noted that in other work [6], the mean sensitivity achieved through graders observation on different set of retinal images was 86%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The best result achieved was sensitivity of 82%. It is worth noted that in other work [6], the mean sensitivity achieved through graders observation on different set of retinal images was 86%.…”
Section: Discussionmentioning
confidence: 99%
“…However, the manual processing of retinal images is labour intensive. The accuracy of the screening is also subject to the graders observation [6]. The automation, or partial automation, of the process is therefore desirable although the complexity of drusen detection hampers such automated screening, especially in the case of early stage AMD when the presence of drusen is often difficult to detect.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study suggests that non-stereo digital fundus images are safe and valid for screening for ARMD. 7 A further report demonstrated that electronic referral of patients with ARMD accompanied by digital images significantly reduced referral delays, speeding up access to photodynamic therapy treatment, and resulting in improved visual outcome. 8 …”
Section: Macular Diseasementioning
confidence: 99%
“…1 We believe this technique offers significant advantages in decreasing the time from referral to treatment especially with the advent of new treatment modalities for AMD. We read with keen interest the paper by Jain et al describing the successful use of non-stereo digital fundus photographs for screening for AMD.…”
mentioning
confidence: 99%
“…We read with keen interest the paper by Jain et al describing the successful use of non-stereo digital fundus photographs for screening for AMD. 1 Screening in medicine is defined as a method of detecting disease at a very early stage before it produces any signs or symptoms. In the case of screening for AMD, the aim is to prevent or modify a disease that can cause severe vision loss.…”
mentioning
confidence: 99%